ChemInform Abstract: Multisubstituted Benzo[b]furans Through a Copper‐ and/or Palladium‐Catalyzed Assembly and Functionalization Process. Issue 25 (3rd June 2013) - Arcadi, Antonio; Blesi, Federico; Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Marinelli, Fabio
Abstract A straightforward general protocol for the synthesis of 2, 5, 7‐trisubstituted benzo[b]furans from readily available 2‐chloro‐ or 2‐bromo‐6‐iodo‐4‐substituted phenols is described and the subsequent functionalization in 7‐position using established cross‐coupling reactions is studied.